(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Now a day’s sports business and organization must invest in their human recourses for the effective and efficient organization of the operation (Khasawneh, 2011). The youth and sports offices have a responsibility to build and organize human resources to capable of sustainable sports development. However, the researcher observed the human resource management department of a sports organization unable to properly put in practice the function of human resource management practices. Due to that the expansion and development of sports became awkward and not sustainable in Amhara region, Ethiopia. The main finding of this study was to investigate the major challenges of human resources management on expansion and development of sports in Amhara region, Ethiopia. As a result of the mean percentage indicated 90.26 respondents respond the human resource management practices is low and puts the human resources management practices under the first quartile this, prevailed that the human resource management practices effect to the development of sport is low. The present study also identified there was a significant moderate positive association between reward, employee training, and sports development. Yet, weak positive association exhibited between hiring and selecting, working condition of human resource management function and sports development. The regression result depicted that R= 0.462(46.2), it means that the human resource development management functions practiced in sports organization below half and not satisfactory. Meanwhile, the researcher confirmed through multiple regression each human resources function predict the potential for sports development and in the result, the working condition and reward system has a significant effect on sports development. On the other hand, performance appraisal and employees training have shown insignificant role and remain major challenges for the development of the Amhara region, Sport in Ethiopia.